Tracheal Stenting for Malignant Tracheoesophageal Fistula: A Case Report with review of literature - Bhattarai, Shachee; Thakur, Binay (Nepalese Journal of Cancer, 2025)
Background: Malignant tracheoesophageal fistula (mTEF) is a serious complication of advanced esophageal cancer, often the result of tumor eroding into the airway. Without prompt intervention, aspiration and respiratory compromise can rapidly become life threatening.Case: We describe a 76 year old male with middle esophageal squamous cell carcinoma, previously treated with chemo-radiotherapy and immunotherapy, followed by semi covered self-expanding metallic stent (SEMS) placement in esophagus for palliation of dysphagia. Due to tumor spread above esophageal SEMS causing dysphagia, stent over stent was placed. Later he developed mTEF, 3 cm above carina of about 1 cm diameter with upper margin of esophageal SEMS just below the fistulous opening. A 6 cm long fully covered tracheal SEMS was deployed via rigid bronchoscopy to seal the defect, accompanied by percutaneous endoscopic gastrostomy (PEG) placement to secure enteral nutrition. His symptoms resolved immediately, and follow-up at two months showed the stent remained well positioned.Conclusion: For patients with advanced esophageal cancer and mTEF due to tumor invasion, rigid bronchoscopy guided fully covered tracheal stenting offers rapid airway protection and effective palliation, especially when esophageal stenting is not feasible or it fails.